Cross‐sectional and prospective relation of cannabis potency, dosing and smoking behaviour with cannabis dependence: an ecological study. (17th March 2014) - van der Pol, Peggy; Liebregts, Nienke; Brunt, Tibor; van Amsterdam, Jan; de Graaf, Ron; Korf, Dirk J.; van den Brink, Wim; van Laar, Margriet
Abstract Background and Aims Increased delta‐9‐tetrahydrocannabinol (THC) concentrations in cannabis may lead to higher THC exposure, cannabis dependence and treatment need, but users may also adapt the actual intake of THC through reduced inhalation of THC containing smoke (titration). We investigated whether consumers of stronger cannabis use less cannabis per joint or inhale less smoke than those using less potent cannabis and whether these factors predict cannabis dependence severity. Methods Heavy cannabis users (n = 98) brought their own cannabis, rolled a joint and smoked it ad libitum in a naturalistic setting. We analysed the content of the joint, its association with smoking behaviour and the cross‐sectional and prospective (1.5‐year follow‐up) relations between smoking behaviour and cannabis dependence severity (total number of DSM‐IV dependence symptoms). Results THC concentration in cannabis (range 1.10–24.70%) was correlated positively with cannabis dose per joint (b = 0.008, P = 0.01), but the resulting THC concentration per joint (range 0.24–15.72%) was associated negatively with inhalation volume (b = −0.05, P = 0.03). Smoking behaviour measures (number of puffs, inhaled volume, reduction of puff volume and puff duration while smoking) predicted follow‐up dependence severity, independently of baseline dependence severity and monthly THC dose (number of joints × cannabis dose × cannabis THC concentration). Monthly THC dose only predicted follow‐up dependence severity when unadjusted for baseline severity. Conclusions Cannabis users titrate their delta‐9‐tetrahydrocannabinol intake by inhaling lower volumes of smoke when smoking strong joints, but this does not fully compensate for the higher cannabis doses per joint when using strong cannabis. Thus, users of more potent cannabis are generally exposed to more delta‐9‐tetrahydrocannabinol. Smoking behaviour appears to be a stronger predictor for cannabis dependence severity than monthly delta‐9‐tetrahydrocannabinol dose.